REVISED STATUTES OF THE STATE OF WISCONSIN, PASSED AT THE EXTRA SESSION OF THE LEGISLATURE COMMENCING JUNE 4, 1878, AND APPROVED JUNE 7, 1878, at 1121, ch. 196, sec. 4834 (1878) - (:unkn) unknown (General Publisher, 1878)
Prohibited the carry of any dirk, dagger, sword, pistol, or other offensive or dangerous weapons. Violators required to post sureties for a term not exceeding six months, with right of appeal.
--
Keywords: SURETY